Nutrient Intake and Physical Exercise as Modulators of Healthy Women - Rocha-Rodrigues, Sílvia; Afonso, José; Sousa, Monica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cumulative evidence demonstrates that healthy nutrient intake and regular physical exercise are both powerful lifestyle strategies that modulate lifelong health through their ability to improve body composition, musculoskeletal health, sex steroid hormones, sleep quality, and physical and cognitive performance, as well as to prevent chronic diseases across the lifespan, especially in women. While the benefits of nutrition and physical exercise are commonly studied separately, the integration of nutrition and physical exercise has the potential to produce greater benefits in women than strategies focusing only on one or the other. Studying the specificities of women in response to interventions is of the utmost importance for providing optimal healthcare and aids the design of guidelines that are better suited for women. A better knowledge regarding nutrient intake and physical exercise and their interaction in women is therefore needed. This Special Issue entitled "nutrient intake and physical exercise as modulators of healthy women" will comprise manuscripts that highlight this integrational approach as a potential modulator of lifelong outcomes in women.